Pengetahuan Dan Perilaku Mahasiswi Fakultas Kedokteran dan Farmasi Universitas Cenderawasih Dalam Upaya Pencegahan Kanker Serviks - Elsye Gunawan; Gerson Andrew Warnares (Pharmacy Faculty, Universitas Muhammadiyah Purwokerto, 2018)
The Study of Global Burden of Diseaase Cancer Collaboration shown In 2015, there were 17.5 million cancer cases worldwide and 8.7 million deaths. Aims of this research to find out the knowledge level and behavior the female students of medicine and pharmacy Uncen in efforts prevention of cervical cancer. This research is non experimental research which is analyzed descriptively. Cross sectionel design where data collection was done only one and data collection in August 2017 by survey method and questionnaire as research instrument. The location of the research was done in the faculty of medicine and program study of pharmacy Cenderawasih University. The results obtained from this study were total of 359 female students, age 22 respondents (23.12%), unmarried 98.89%, respondents from jayapura, living with parents, often discussing with family, especially mother, and they talked about reproductive health. the most respondents get information about cervical cancer prevention from lecturer's subjects that is 63,79%, electronic media 57,94% and 55,99% get information from print media. The conclusion of this research is the level of female student knowledge about cervical cancer, cervical cancer prevention and cervical cancer prevention behavior of female students of Faculty of Medicine and Pharmacy study program of Cenderawasih University is considered good.